Prevalence of Portal Vein Thrombosis in Budd-Chiari Syndrome Patients - Moeen Ul Huq, Aymen Jamal, Muhammad Zain Akhtar, Ammarah Tassudaq, Muhammad Faisal Bacha, Tahir Mukhtar Sayed (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: Thrombosis of the portal vein or obstruction of the hepatic venous outflow tract is the cause of portal vein thrombosis (PVT) and Budd-Chiari syndrome (BCS). Patients with PVT may experience a shorter survival rate compared to those without. The present study aimed to determine the portal vein thrombosis occurrence in Budd-Chiari syndrome patients. Patients and Methods: This cross-sectional study was conducted on 46 Budd-Chiari syndrome patients in Gastroenterology department of DHQ Teaching Hospital and Mufti Mahmood Memorial Hospital, Dera Ismail Khan from November 2021 to October 2022. Written informed consent was taken from each individual. Doppler ultrasonography (colored-pulsed) was used to confirm the PVT and BCS cases. Clinical data, laboratory findings, and radiological data were recorded. SPSS version 26 was used for data analysis. Results: The overall mean age of the BCS patients was 28.34±4.6 years. The prevalence of portal vein thrombosis in BCS patients was 12.8% (n=6). Of the total cases, the incidence of chronic and acute BCS presentation was 42 (91.3%) and 4 (8.7%) respectively. The most prevalent symptoms of BCS were abdominal pain and abdominal enlargement in 38 (82.6%) and 41 (89.1%) respectively. Hepatomegaly and ascites were most prevalent clinical signs found in 36 (78.3%) and 37 (80.4%) respectively. The incidence of esophageal varices, gastric extension, and fundal varices were 32 (69.6%), 4 (8.7%), and 2 (4.3%) respectively. About 21 (45.7%) cases had Portal hypertensive gastropathy (PHG). Conclusion: A higher incidence of PVT was observed in the present study than previously reported. Sociodemographic data and underlying etiology of BCS were not significantly different between patients with and without PVT. Those with PVT were more likely to experience hepatic tenderness, increased white blood cells, and increased direct bilirubin. PVT and other patients had similar Doppler ultrasound findings. Keywords: Portal vein thrombosis, Prevalence, Budd-Chiari syndrome